KARAKTERISTIK BIOPELET BERDASARKAN KOMPOSISI SERBUK BATANG KELAPA SAWIT DAN ARANG KAYU LABAN DENGAN JENIS PEREKAT SEBAGAI BAHAN BAKAR ALTERNATIF TERBARUKAN - Lamanda, D. Dhuha; Setyawati, Dina; haida, Nur; Diba, Farah; Roslinda, Emi (Universitas Tanjungpura, 2015)
The research aims to evaluate the quality of biopellets made from different composition of the oilpalm trunk powder and Laban wood charcoal with different type of adhesive. The composition consist of 25% oilpalm powder : 75% Laban wood charcoal; 50% oilpalm powder: 50% Laban wood charcoal; 75% oilpalm powder : 25% Laban wood charcoal; 100% oilpalm powder respectively. The adhesives used are tapioca flour and sago flour. The research used completely factorial randomized design, which consists of eight combination treatment with 3 replications. The material was mixed manually and biopellets produced with meat mincer in home scale with size 2 cm long and diameter 0.4 cm.Â Biopelet then dry in oven for 24 hour with temperature 600C-700C. The quality of biopelet was evaluate according to SNI 8021 : 2014. The result of research showed that the average values of water content of biopellets was range between 6.91% - 9.98%; the average values of ash content was range between 1.02% - 1.69%; the average values of volatile matter content was range between 38.36% - 71.93%; the average values of fixed carbon content was range between 26.45% - 59.97% and the average values of calor was range between 3719,67(cal/g) â€“ 5944,33 (cal/g). The composition of oilpalm and Laban wood charcoal and type of adhesives was significantly affected the calor value of biopellets. Meanwhile the other values such as moisture content, ash content, volatile matter content and fixed carbon content was not significant. The quality of biopellets can fulfill the SNI 8021 : 2014 standard, except on ash content. The best biopellets was achieved on composition 25% oil palm trunk powder : 75% Laban wood charcoal with adhesive tapioca. Keywords : Biopellets, Laban wood, Oilpalm trunk, tapioca, sago